AIRR Community Standardized Representations for Annotated Immune Repertoires - Vander Heiden, Jason Anthony; Marquez, Susanna; Marthandan, Nishanth; Bukhari, Syed Ahmad Chan; Busse, Christian E.; Corrie, Brian; Hershberg, Uri; Kleinstein, Steven H.; Matsen IV, Frederick A.; Ralph, Duncan K.; Rosenfeld, Aaron M.; Schramm, Chaim A.; et al. (Frontiers in Immunology, 2018)
Increased interest in the immune system's involvement in pathophysiological phenomena coupled with decreased DNA sequencing costs have led to an explosion of antibody and T cell receptor sequencing data collectively termed “adaptive immune receptor repertoire sequencing” (AIRR-seq or Rep-Seq). The AIRR Community has been actively working to standardize protocols, metadata, formats, APIs, and other guidelines to promote open and reproducible studies of the immune repertoire. In this paper, we describe the work of the AIRR Community's Data Representation Working Group to develop standardized data representations for storing and sharing annotated antibody and T cell receptor data. Our file format emphasizes ease-of-use, accessibility, scalability to large data sets, and a commitment to open and transparent science. It is composed of a tab-delimited format with a specific schema. Several popular repertoire analysis tools and data repositories already utilize this AIRR-seq data format. We hope that others will follow suit in the interest of promoting interoperable standards.